THE ROLE OF THE RADIO-BASED ON-AIR TAHFIDZ PROGRAM IN STRENGTHENING MOTIVATION AND CONSISTENCY OF STUDENTS' MURAJA'AH OF AL-QUR'AN MEMORIZATION AT MA SAINS BINA INSAN KAMIL TUBAN - Ulmi Farihah; M. Fauzi (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This research is motivated by the low motivation, discipline, and consistency of students' recitation of the Qur'an in memorization learning, so that learning innovations are needed that can increase student enthusiasm and involvement in a sustainable manner. As an effort to address this problem, MA Sains Bina Insan Kamil Tuban developed a radio-based On-Air Tahfidz Program as an interactive, educational, and inspiring tahfidz learning medium. This study aims to describe the implementation of the On-Air Tahfidz Program, analyze its role and impact on students' motivation and consistency of recitation, and examine the program's implementation through a SWOT analysis. This study uses a qualitative method with a case study approach. The research subjects consisted of the madrasah principal, tahfidz assistant teachers, radio operators, and student participants in the program. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawing, while data validity was obtained through source and technique triangulation. The research results show that the On-Air Tahfidz Program was implemented systematically through planning, broadcasting, intensive guidance, and periodic evaluation. This program has been proven to increase students' learning motivation, discipline, self-confidence, and consistency in their recitation, as well as helping improve the quality of their Quran reading and memorization. A SWOT analysis shows that the program has significant strengths and opportunities to be developed as a media-based tahfidz learning innovation in madrasah environments.